Efficiency change over time in a multisectoral economic system - Mikuláš Luptáčik; Bernhard Mahlberg (University of Economics in Bratislava, Department of Economic Policy, 2012)
Neoclassical growth accounting is a methodology used to measure the contribution of different production factors to economic growth and to indirectly compute the rate of technological progress. This model assumes constant returns to scale and perfectly competitive factor markets, which implies that factor prices are equal to marginal products – something that is only satisfied if factor markets are cleared, and external effects and distortions are absent. However, these conditions are usually not satisfied in real economies. Moreover, growth accounting assumes efficiency on factor and commodity markets, and consequently does not distinguish between efficiency change and technical change. In this paper, we estimate total factor productivity growth without recourse to data on factor input shares or prices. In the proposed model, the economy is represented by the Leontief input-output model, which is extended by the constraints of primary inputs. A Luenberger productivity indicator is proposed to estimate productivity change over time; this is then decomposed in a way that enables us to examine the contributions of individual production factors and individual outputs to productivity change. The results allow the inference of which inputs or outputs of an economy are the drivers of the overall productivity change– this is then decomposed into efficiency change and technical change components. Using input-output tables of the US economy for the period 1977 to 2006, we show that technical progress is the main source of productivity change. Technical progress, in turn, is mostly driven by capital whereas low-skilled labor contributes negatively.
Keywords: O47; C43; C61; C67; 330; Neoclassical Growth Accounting; Multi-Objective Optimization; Productivity Change; Efficiency Change; Luenberger Indicator